Forensic Audit Practices to Improve Students' Understanding of Anti-Corruption - Rony Uncok Cahyadi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Corruption is a major problem that must be resolved in Indonesia. The number of corruption cases in Indonesia is increasing, and Indonesia's Corruption Perception Index is only 34. Of course, this achievement is still far from expectations; concrete actions are needed to raise public awareness and participate in the process of resolving corruption in Indonesia. This community service activity was carried out at STIE GICI Bekasi. This activity was attended by 12 students from STIE GICI, Bekasi, with the purpose of improving the ability to detect and prevent corruption. This community service employed a case study design because the focus is on the effectiveness of anti-corruption strategies. The results of this PKM are expected to increase students' understanding of the benefits of forensic audits in detecting and preventing potential corruption. The implication of this activity is an increase in anti-corruption understanding among the younger generation.